Analisis Efektivitas Pengelolaan Aset pada Bagian Umum Sekretariat Daerah Kabupaten Jombang - Shavira, Shavira Aulia Safitri; Susi Hardjati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The delegation of authority that was originally handled by the central government and then transferred to the local government resulted in an increase in the authority of the local government when regional autonomy was implemented. Among these authorities is the management of regional property. The government has issued a number of regulations relating to the management of regional property to improve the way state or regional property is managed to facilitate the realization of good governance in the implementation of regional autonomy. The General Section is a government organization under the auspices of the General Administration Section of the Regional Secretariat of Jombang Regency. Its duties include assisting the General Administration Assistant in planning work programs, organizing and repairing household goods, and organizing leadership and regional equipment arrangement programs. Most of the assets owned and supervised by the General Section are assets used to support significant operational activities in other Regional Apparatus Organizations (OPD). Knowing how well asset management in the General and Regional Assets Section of the Regional Secretariat of Jombang Regency is the purpose of this research. Documentation is the data collection method used in this study. The analysis of this study used an effectiveness scale and descriptive statistics. Planning and budgeting for the needs, purchases, and use of the General Section are the results of this study, and are carried out administratively in accordance with applicable laws. However, from the results of the analysis, asset management in the General Section is still not effective.